Makna Sosial Program PKH dalam Rangka Mewujudkan Kesejahteraan Rumah Tangga Miskin di Desa Kedungpari, Jombang - annisa annisa; Muhammad Nur Hidayat; Nieke Rudyanty Winanda (PANOPTIKON: Jurnal Ilmu Sosial dan Humaniora, 2022)
Program keluarga harapan is a conditional social assistance program by the government aimed at poor families designated as PKH beneficiary families. Meanwhile, in the implementation of this PKH social assistance program experienced many cases about the misuse or transfer of the function of funds that have been given to beneficiaries. The action is caused by two motives, namely the motive of cause and motive of purpose. This study sought to find out the social context behind the individual in the process of susing the PKH card, as well as to find out the actions of individuals in the behavior of pawning PKH cards. The study used Alfredz Schutz's phenomenological approach. The selection of informants uses purposive techniques with individual criteria that are included in the PKH assistance recipient members of 8 people. The results of the study on the ground there are four motives in the pawning of PKH cards, namely 1) to carry out pawning with a motive in debt. 2) perform pkh card pawning with lifestyle and social status motives. 3) Social Dilemma of Beneficiaries. 4) Save Borrow Between PKH members.